Cancer of Unknown Primary origin in the genomic era: Elucidating the dark box of cancer. Issue 7 (July 2015) - Economopoulou, Panagiota; Mountzios, Giannis; Pavlidis, Nicholas; Pentheroudakis, George
Abstract : Highlights: Gene expression profiling (GEP) assays assign Cancer of Unknown Primary (CUP) cases to the most likely tissue of origin. A survival benefit in CUP patients managed with tissue-specific antineoplastic therapy after use of a GEP assay is unproven. There is no consensus on the most cost-effective way to incorporate the GEP CUP assays in the current diagnostic algorithm. The search for a CUP molecular signature responsible for its atypical behavior has not been done systematically. Regarding targeting, the assumption that the same gene mutation matters in the same way across tumor types is unproven. Abstract: Cancer of Unknown Primary (CUP) comprises a heterogeneous disease group with diagnosis of metastatic malignancy in the absence of an identifiable primary site after diagnostic work up. CUP may either resemble a specific primary tumor site sharing common clinicopathological characteristics and prognosis, or present as a distinct disease entity with undifferentiated pathological features, usually bearing dismal prognosis. Diagnosis and management have traditionally been based on clinicopathological characteristics and therapeutic strategies have been mainly empirical. In the last decade, the advent of massive gene sequencing and the advances in genomic technologies have shed light on the genomic landscape of CUP. Several gene panel tests are currently commercially available and are used in an effort to correlate the genomic characteristics of a specific CUP tumor to those of a known primary tumor, guiding thus therapeutic management. Nevertheless, these efforts are hampered by the rarity of CUP and the inability to validate the results of such tests due to the paucity of randomized clinical trials. In the current work, we provide an overview of CUP with emphasis on the impact of the genome sequencing technologies on diagnosis and management of these tumors. We also discuss potential implications of genomics for the future treatment of CUP and address the challenges of the implementation of these therapeutic strategies in routine clinical practice.